(untitled) - Wallace, Robert A. (New York, 1996)
A comprehensive text providing a current study of genetics, molecular biology, and immunology. This fourth edition has a new illustration programme developed by a group of science textbook artists. The book moves from the cellular level to molecular biology, heredity, and evolution, so as to prepare students for later discussions about micro-organisms, plants and animals.
Keywords: Biology